The study of customer commitment on relationship quality in Agrobank, Jerantut / Azrian Azrina Ideris - Ideris, Azrian Azrina (Faculty of Business and Management, 2009)
The purpose of the study is to investigate the customer commitment on relationship quality in Agrobank, Jerantut. This research aims to the study about the commitment among the customer to enhance relationship quality in Agrobank, Jerantut. The literature, define customer commitment as an exchange partner's willingness to maintain an important enduring relationship (Garbarino & Johnson, 1999; Hennig-Thurau et al., 2002). In order to measure customer commitment in Agrobank, the researcher refers to loyalty and involvement elements. Loyal customer shows that they have commitment to enhance relationship quality in Agrobank ,Beside that, customer involvement can show the effort of customer to maintain relationship with Agrobank. The researcher was distributed 40 questionnaires that consist of 20 questions to the respondents. Only 30 questionnaires were selected by researcher for academic purpose. From the finding most of the respondents showed that they loyal with Agrobank, but majority of them does not give involvement whether by directly or indirectly with Agrobank. In conclusion, Agrobank only used customer commitment to make them loyal with Agrobank’s products and services, and ignoring the customer involvements in Agrobank’s activities, products and services.